(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper investigates the effectiveness of two mnemonic techniques, keyword and first-letter mnemonics, in enhancing memory performance. Mnemonic strategies have long been utilized to aid memory retention, and this study seeks to revisit their efficacy in contemporary educational contexts. The study employs a comparative design, examining the differential impact of keyword and first-letter mnemonic techniques on memory performance when compared to traditional rote learning. The research begins by assessing the initial memorization process on the first day, where participants are randomly assigned to one of two groups: traditional learning and learning with mnemonics. The traditional group follows the rote learning approach, while the experimental group uses mnemonics designed by the researcher, incorporating both first-letter and keyword techniques. Participants in each group are presented with materials to memorize, and their performance is evaluated through recall tasks. Preliminary findings suggest that both keyword and first-letter mnemonic techniques significantly enhance memory performance compared to traditional rote learning. However, further analysis aims to identify any nuanced differences between the two mnemonic strategies and their respective impacts on memory encoding, retention, and recall. This research contributes to the ongoing discourse on memory enhancement techniques within the fields of cognitive psychology and educational psychology. By providing empirical evidence on the efficacy of mnemonic methods, educators and learners can make informed decisions regarding the adoption of mnemonic strategies to optimize learning outcomes.